Connectivity of organic matter pores in the Lower Silurian Longmaxi Formation shale, Sichuan Basin, Southern China: Analyses from helium ion microscope and focused ion beam scanning electron microscope - Zhang, Kun; Jiang, Shu; Zhao, Rui; Wang, Pengfei; Jia, Chengzao; Song, Yan (Geological journal (Chichester, England), 2022)
As one of the most important energy sources in the world today, shale gas has attracted extensive research. Numerous scholars agreed that the organic matter (OM) pores in shale provide the main space which benefits effective gas occurrence. However, the connectivity provided by OM pores is more important in the development process than their reservoir properties. A comprehensive portrayal of the 3D connectivity of the OM pores is elaborated in this study. The Lower Silurian Longmaxi shale samples were selected as the research subject. The shale samples are subjected to focused ion beam scanning electron microscope, helium ion microscope observation experiments, 2D microscopic characterization of OM pores, and 3D segmentation extraction. The results indicate that the connectivity of shale is mainly contributed by OM pores. The OM pores have the advantageous structural characteristics of large number per unit area, evenly distributed, regular pore morphology, and large pore size relative to the mineral matrix pores. The OM pores structure in shale is complex with a network structure of small pores nested in large pores, which can increase the adsorption capacity of gas. Besides, the small pores nested in large pores can act as a throat to significantly improve the connectivity. OM pores in the pyrobitumen are interconnected in 3D space, providing the main channels for gas percolation in the shale reservoir. Organic matter pores have a large number of pores per unit area and are characterized by uniform distribution, regular morphology, and large pore size. The organic matter pores of shale have a composite network structure, with large pores nested in small pores, improving the connectivity of the system. The large size organic matter pores in the pyrobitumen scorched bitumen are interconnected, providing the main channel for gas percolation in the shale reservoir.